Using a Critical Literacy Approach in the EFL Class - Farralelli, Mariana (Journal of NELTA, 2010)
Thinking critically is an ability which is to be developed in the EFL class as a result of the generalized process of globalization, immigration and poverty. It is essential for teachers to be aware of the fact that tolerance, dialogue among cultures and deconstruction of texts need to be exercised so that students can dissect dominant discourses and allow for diversity knocking down stereotypes. What follows is a detailed guide of all those aspects teachers should take into account if they are to indicate in their students a critical way to approach reality. Key words: critical literacy, thinking skills, power relations, discourse DOI: 10.3126/nelta.v14i1.3088 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 26-31